Organic Food: The Factors Influencing Consumers' Purchasing Intention - Rakotoarisoa Maminiaina Heritiana Sedera; Ronaldo Yolanda Putra; Eka Kurnia Saputra; Muhammad Ahmad Ali (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This investigation assessed the factors determining consumers' purchasing intention for natural food. This study employs four variables to explain the phenomenon: purchasing intention toward organic food, altruistic value, egoistic value, and attitude toward organic products. Design/Methods/Approach: This study employs a quantitative approach, using primary data collected through an online survey from a sample of 109 individuals. We use the convenience sampling method to collect the data. Furthermore, the regression analysis is performed with SPSS version 23. Findings:  The findings of this study highlighted that altruistic and egoistic values do not influence the intention to purchase organic food. Consumers' attitude has a significant influence on purchasing organic food. However, egoistic values and altruistic values do not influence purchasing intention. Originality/Value: This research examines specific parameters determining consumers' purchasing behavior toward organic products. The model in this work is grounded with a few gaps that still need to be explored and have rarely been investigated in past studies. Practical/Policy implication: The findings contribute an additional theoretical comprehensive to the organic food consumption literature. Moreover, these findings can be an asset to the practitioner in shaping successful marketing strategies to promote and develop organic food. This study can provide additional knowledge and a new perception of consumer behavior toward organic food.